Kinetic properties of “dual” orexin receptor antagonists at OX1R and OX2R orexin receptors - Callander, Gabrielle E.; Olorunda, Morenike; Monna, Dominique; Schuepbach, Edi; Langenegger, Daniel; Betschart, Claudia; Hintermann, Samuel; Behnke, Dirk; Cotesta, Simona; Fendt, Markus; Laue, Grit; Ofner, Silvio; et al. (Frontiers in Neuroscience, 2013)
Orexin receptor antagonists represent attractive targets for the development of drugs for the treatment of insomnia. Both efficacy and safety are crucial in clinical settings and thorough investigations of pharmacokinetics and pharmacodynamics can predict contributing factors such as duration of action and undesirable effects. To this end, we studied the interactions between various ‘dual’ orexin receptor antagonists and the orexin receptors, OX1R and OX2R, over time using saturation and competition radioligand binding with [3H]-BBAC ((S)-N-([1,1'-biphenyl]-2-yl)-1-(2-((1-methyl-1H-benzo[d]imidazol-2-yl)thio)acetyl)pyrrolidine-2-carboxamide). In addition, the kinetics of these compounds were investigated in cells expressing human, mouse and rat OX1R and OX2R using FLIPR® assays for calcium accumulation. We demonstrate that almorexant reaches equilibrium very slowly at OX2R, whereas SB-649868, suvorexant and filorexant may take hours to reach steady state at both orexin receptors. By contrast, compounds such as BBAC or the selective OX2R antagonist IPSU ((2-((1H-Indol-3-yl)methyl)-9-(4-methoxypyrimidin-2-yl)-2,9-diazaspiro[5.5]undecan-1-one) bind rapidly and reach equilibrium very quickly in both binding and / or functional assays. Overall, the “dual” antagonists tested here tend to be rather unselective under non-equilibrium conditions and reach equilibrium very slowly. Once equilibrium is reached, each ligand demonstrates a selectivity profile that is however, distinct from the non-equilibrium condition. The slow kinetics of the dual antagonists tested suggest that in vitro receptor occupancy may be longer lasting than would be predicted. This raises questions as to whether pharmacokinetic studies measuring plasma or brain levels of these antagonists are accurate reflections of receptor occupancy in vivo.